Raden Ajeng Kartini’s Letters as Reflected in Social Feminism - Agnes Widyaningrum (Dinamika Bahasa dan Budaya, 2016)
Raden Ajeng Kartini is one of Indonesian heroines who lived in early 1900. She is the pioneer in woman’s emancipation in Indonesia. Her brilliant and encouraging ideas for women are written in her letters. Learning from her letters is a good way to realize that women nowadays are not living in the darkness era but brightness era. Kartini has done something remarkable at that time though she was imprisoned because she is a woman. She wrote that she was living surrounded by thick walls during her growth from a girl to a woman. The world outside was out of her reach because the Javanese tradition forbid a girl and woman to go outside of their homes especially for royal families. Her reading help her thinking that women should not give up to fight for their freedom because women also have their rights like the right to choose their future husband, to get education and to work. She has written letters to her close friends in Netherlands and those letters are compiled into a remarkable writing containing many wise lessons especially for female. According to Barbara Ehreinrich (1976) that the socialist and feminist both have something in common that is they are critical ways of looking at the world. Both rip away popular mythology and “common sense” wisdom and force us to look at experience in a new way. Both seek to understand the world – not in terms of static balances, symmetries, etc. (as in conventional social science) – but in terms of antagonisms. They lead to conclusions which are jarring and disturbing at the same time that they are liberating. There is no way to have a Marxist or feminist outlook and remain a spectator. To understand the reality laid bare by these analyses is to move into action to change it. This article is about an analysis of Kartini’s ten short writings as parts of her letters using socialist feminism. Keywords: socialist, feminist, social feminism